PENGEMBANGAN MEDIA BUKU FLANEL MATEMATIKA UNTUK MENINGKATKAN KEMAMPUAN BERHITUNG PERMULAAN DI KELAS I SDN KASOMALANG VIII - Dilla Syaviah Tsamara; Indhira Asih Vivi Yandari; Trian Pamungkas Alamsyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2022)
This study aims to find out how to develop the Mathematic Flannel Book media to improve arithmetic ability at the beginning of class I at SDN Kasomalang VIII, to determine the feasibility of the Mathematics Flannel Book media, to determine the improvement in initial counting and student responses to the use of Mathematics Flannel Book media in the process of learning activities. The subject in this research is the first grade of Kasomalang VIII elementary school, totaling 19 students. This type of research uses the R&D method which refers to development refers to the adaptation of Sugiyono’s development steps which consists of 9 steps. The instruments used are questionnaires for product validation by a team of experts (media, materials, and learning), pretest and posttest, and student response questionnaire sheets. Based on data analysis, the Mathematic Flannel Book media to improve early numeracy skills in grade I SDN Kasomalang VIII which was developed is included in the Eligible category with a percentage of 80.7% from 2 media experts, Very Eligible category with a percentage of 92.5 from 2 material experts, category Very Eligible with a percentage of 88.75% from 2 learning experts. The increase in initial numeracy for students after using the Mathematics Flannel Book media in learning activities in the first trial obtained an N-gain value of 0.41 and the second trial obtained an N-gain value of 0.62 on the Medium criteria. The response of students to the Mathematics Flannel Book media in the trial with 19 respondents was 93.2%, which was included in the Very Good category.